How Does Place Impact Intrapartum Practice for Midwives and Obstetricians? - Mellor, Christine; Hunter, Marion; Smythe, Elizabeth (Elsevier BV, 2024)
BACKGROUND: Rising rates of labour and birth interventions are causing concern, having the potential to cause harm if used inappropriately. International evidence demonstrates that place itself influences birth outcomes, but evidence is limited as to how. In New Zealand there are differences in the rates of spontaneous vaginal births by place, along with differences when benchmarking uncomplicated primiparae birthing in hospital maternity facilities throughout the country. AIM: To develop understanding of how place influenced midwives' and obstetricians' practice in relation to supporting physiological birth. METHOD: For this Hermeneutic Phenomenological study participants were purposively selected and consisted of nine midwives (employed and self-employed) and three obstetricians, all practising in midwifery led units or hospital maternity facilities. Data was collected using semi-structured interviews. The method of analysis involved writing and rewriting to surface interpretive insights, drawing on philosophical notions from Heidegger and Gadamer. FINDINGS: The findings revealed that place influences what practitioners are attuned to, what is easier for them to achieve, and their ability to provide woman-centred care. Competing tensions and pressures within place can blur the perceived relationship between normality and risk, influencing what is considered to be safe. SUMMARY: Place is not neutral; it influences how midwives and obstetricians practise and shapes how they support physiological labour and birth. The findings of this research contribute to a deeper understanding of the barriers and enablers to supporting physiological birth within place.
Keywords: Aotearoa New Zealand; Birthplace; Hermeneutic phenomenology; Midwives and obstetricians; Physiological birth; Supporting normal birth; 11 Medical and Health Sciences; Obstetrics & Reproductive Medicine; 3215 Reproductive medicine; 4204 Midwifery